Modelling the trawl catching process for fish - Bianchini M.L.; Ragonese S. (Dynamique des populations marines, 1998)
This research is aimed at demonstrating, both analytically and experimentally, that the trawl fishing is size-selective. Given the assumption that speed and stamina are positively related to size, this suggests that the largest size classes are the ones that substantially contribute to the more-than-proportional-to-time catches. A new conceptual model taking into account a size-dependent time lag in the process has been envisaged. Under the assumptions of the model, it appears that (length) frequency distributions from short trawl surveys are not comparable to those coming from much longer commercial hauls, and that population parameters estimated from surveys are potentially biased (proposing a worse scenario than the true situation). In fact, using actual data from Italian trawl surveys, it significantly appears that at least the hake, Merluccius merluccius, behaves as the model suggests.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)